Composição florística, estrutura fitossociológica e conteúdo de nitrogênio foliar em cerradão, Luiz Antônio, SP - Silva, Érico Fernando Lopes Pereira da (2003)
The cerradão is one of the forest physiognomy of the cerrado biome more threaded with the expansion of agricultural activities. The existence of remaining cerradão areas in the state with different sizes and conservation status show the necessity of studies in these areas. In São Paulo state, 237,918 ha of Cerrado Lato sensu are distributed in patches centered in two large regions, the first one, localized in the Central to North-Northeast region and the second, in the West region of the state. The study area was a cerradão patch has 1,735.55 ha, known as Oitocentos Alqueires , situated in Southwest of Estação Ecológica de Jataí in the Luís Antônio municipality, São Paulo state. We used 25 permanent plots of 250 m². The floristic survey characterized the vegetation like a cerradão and the vertical phytosociological parameters permitted us give to the species values through the Relative Sociological Position (RSP) and the Amplified Value of Importance index (AIVI), associating the horizontal phytosociological structure showed by the Value of Importance index (IVI) with the heterogeneity and irregularity of the cerradão strata. We founded that the studied area has a great number of shrub and arboreous individuals (5,284 individuals) beyond a high value of floristic diversity (3.47 nat.ind-1). The diameter and tall distributions showed abundance on the natural regeneration component due the great stock of young plants that compose the inferior stratum of the community. The natural regeneration analysis showed is essential to comprehend the establishment, survival and growth of the cerradão species. The regeneration component demonstrate that the density in the superior class was 700.80 ind.ha-1, in the median, 4,912.00 ind.ha-1 and in the inferior 1,296.11 ind.ha-1. Although the low density in of the inferior class, most of the populations in the cerradão community don t demonstrate regeneration problems and this aspect is clear due the great number of regenerating individuals in the median and superior classes. Using the phytosociological far evaluation of parameters and the rate of natural regeneration we selected 30 species and estimated the nitrate reductase activity (NRA) and the leaf nitrogen content. The analysis of leaf RNA and leaf nitrogen content suggests that the activity of the enzyme is not related with the content of NO3- in the ground and probably the plants of the study area use other nitrogen sources, beyond the NO3-, probably NH4+, that also was the predominant ion in relation to the NO3- in the ground. The 30 species had presented a diversification in the strategies of nitrogen assimilation having used as source, probably, NO3-, NH4+, micorriza and nodulation. How much to the foliar nitrogen tax it is important to stand out that of the ten species of bigger foliar nitrogen content, seven they are Leguminosae, indicating that this family possesss an efficient adaptation in the nitrogen assimilation. Low the correlation of the concentration of íons NO3- of the ground with the RNA confirm the hypothesis of that the species of the study area possess strategies to optimize the nitrogen assimilation, probably using NH4+ in the NO3- non-availability, besides making use of other assimilated mechanisms as nodulation and associations of micorrizas. Key words floristic and phytosociology, cerradão, arboreous and shrub vegetation, natural regeneration, nitrate reductase activity, leaf nitrogen content, NO3-, NH4+.